Convict criminology : inside and out - Earle, Rod (Bristol : Policy Press, 2017)
Convict criminology is a promising new approach to criminology that is rooted in the study of criminology by people who have firsthand experience of imprisonment. This book traces the emergence of convict criminology and explore its potential relevance outside the United States, specifically in the United Kingdom and Europe. Presenting reflective scholarship that combines personal experience with critical perspectives, it examines the ways that prisoners, ex-prisoners, and prison research contribute to knowledge of criminology and the ways that racism, colonialism, and class shape both the penal experience and the social world beyond the prison.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 14, 2016).
Keywords: Criminology; True Crime